Food Allergies - Trends and Challenges in Treatment and Diagnosis - Sawińska, Zuzanna; Sudelska, Katarzyna; Tarsa, Grzegorz; Kępka, Przemysław; Łokczewska-Bojar, Aleksandra; Skotalczyk, Magdalena; Kuziemkowska, Daria; Kużma, Jan; Ben Rhaiem, Rami; Łącka-Majcher, Anna (Journal of Education, Health and Sport, 2023)
Introduction: Food allergies are becoming an increasingly significant challenge for medicine, public health and patients' quality of life. Over the past few decades, there has been an observed increase in the number of cases of food allergies. This has led to heightened interest among scientists, doctors and specialists in various aspects related to the diagnosis and treatment of this condition. With the increasing precision of food allergy diagnosis, it is necessary to adjust the therapy to the individual needs of patients. Aim of the study: The aim of our study is to summarize the trends and challenges in treatment and diagnosis of food allergies. We focused on current diagnostic methods and treatment options, as well as new promising therapeutic approaches. State of knowledge: In molecular or component-resolved diagnostic tests (CRD), specific IgE antibodies are measured for individual food allergenic molecules. This presents an opportunity to improve specificity for selected foods. Studies have shown that the Basophil Activation Test (BAT) exhibits higher specificity than skin prick tests (SPT) and s-IgE tests, while maintaining its sensitivity. BAT relies on flow cytometry, where the expression of activation markers on the surface of basophils stimulated by an antigen is measured. Due to the existing limitations of certain tests, Oral Food Challenge (OFC) is still considered the gold standard for diagnosing IgE-mediated food allergies. Summary: Research shows that the foundation of diagnosis is the patient's medical history, including a properly collected interview, which should then guide the doctor towards appropriate tests. An elimination diet based on the clinical interview should be implemented until significant relief of allergy symptoms is achieved.